IMF Staff papers : Volume 11 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1964)
This paper describes steps taken by the Venezuelan Government to meet the balance of payments crisis which developed from 1958 to 1960. In addition to balance of payments considerations, several factors associated with the development policies of the Government were considered in establishing the exchange rate. Petroleum exports have long played a dominant role in the balance of payments of Venezuela, accounting for more than 90 per cent of export earnings. The results achieved reflected the characteristics of Venezuela, particularly the balance of payments advantages and the strong tax base in an economy dominated by the petroleum industry. Nevertheless, the experience of the Venezuelan authorities provides a case study of the complexities and difficulties of exchange control devices and multiple exchange rates. It also illustrates the successful operation of monetary, fiscal, and exchange policies in overcoming balance of payments difficulties. In addition, examination of this experience casts some light on the economic effects of measures taken to control the balance of payments.